THE INFLUENCE OF CAPITAL ADEQUACY, LIQUIDITY, BANK SIZE, AND PROFITABILITY ON CREDIT RISK IN COMMERCIAL BANKS CATEGORY BOOK IV - Jummaini; Yanita; Ristati; Pratiwi, Rati (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2023)
Banks play a crucial role in the economy of a country, especially in developing nations like Indonesia. Commercial banks classified as BUKU IV are the largest banking group in Indonesia and are known for their strong management. This research aims to analyze the influence of capital adequacy, liquidity, bank size, and profitability on credit risk in Commercial Banks classified as BUKU IV during the period of 2015-2020. The independent variables consist of CAR, LDR, BS, and ROA, while the dependent variable is NPL (Non-Performing Loans). Secondary data collected by the researcher from the annual financial reports of BUKU IV commercial banks are utilized in this study, employing a census sampling technique. The data analysis method applied is panel data regression using E-Views 10 software. The research results indicate that ROA has a negative and significant effect on NPL in BUKU IV Commercial Banks. However, CAR, LDR, and BS do not have a significant impact on NPL in BUKU IV Commercial Banks.